Ecclesiology Model in Asian Public Theology - Denar, Benediktus; Jew, Jean Loustar; Nirmala, Fransiska Rosari (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
This article attempted to answer the problem formulation, how does the model of ecclesiology based on Asian public theology? Based on this problem formulation, this article aimed to discuss Felix Wilfred's views on Asian public theology, ecclesiological model that is relevant to the perspective of Asian public theology, and the practical implications of the idea on Asian public theology for Church pastoral work. Using a literature study approach, the author attempted to read and explore several of Wilfred's important works on Asian public theology. The result showed that public theology moves outward and opens itself up (inclusive) to meet, embrace and collaborate with others outside the Christian community. Wilfred's Asian public theology perspective always comes from concrete situations, so it is often referred to as subaltern theology.